Etika Amar Makruf Nahi Munkar Dalam Perspektif Hadis - Praduhanda, Faizal (UIN Sumatera Utara Medan, 2024)
Among Muslim communities, Amar Ma'ruf Nahi Munkar is often used in the jargon of Islamic da'wah, which takes the form of religious doctrine, conveying the truth and opposing all forms of religious doctrine, conveying the truth and opposing all forms of tyranny and injustice. This term is also often used as justification for the rejection of all matters related to actions that deviate from religious norms, and justifies actions carried out in the name of religion. The primary data source for the researcher's research is using the six main books of hadith, including Shahih Bukhari Shahih Muslim, Sunan Abu Daud, Sunan At Tirmidhi, Sunan An Nasa'i, Sunan Ibnu Majah, apart from the author will also refer to the Mausu'ah software al-Hadith al-Sharif. The hadith transmitters were traced using the inventory of the Rijal al-Hadith book. In order to make it easier to search for related hadiths and their transmitters, researchers also use the help of Al-Maktabah alSyamilah software. Thus, it can be concluded that the entire range of narrators in the Ḥadiṡ sanad are muttashil. So, here it is clear that the quality of this Ḥadiṡ sanad is Sahih Li Dzatihi. because of all the narrators, not a single one was dropped by Jarh and Ḥadīṡ. This sanad of hadith continues from mukharrij to Rasulullah. Amar Ma'ruf Nahi Munkar's ethics, according to the hadith of Ibn Majah's history, which the author has examined for quality and quantity, consists of three types of methods, namely first, with wisdom which according to Imam Abdullah bin Ahmad Mahmud An-Nasafi is preaching using correct and certain words, namely fair in explaining the truth and eliminating doubts.